Trajectories of Lung Function during Childhood - Belgrave, Danielle C. M.; Buchan, Iain; Bishop, Christopher; Lowe, Lesley; Simpson, Angela; Custovic, Adnan (American Journal of Respiratory and Critical Care Medicine, 2014)
Rationale: Developmental patterns of lung function during childhood may have major implications for our understanding of the pathogenesis of respiratory disease throughout life. Objectives: To explore longitudinal trajectories of lung function during childhood and factors associated with lung function decline. Methods: In a population-based birth cohort, specific airway resistance (sRaw) was assessed at age 3 (n = 560), 5 (n = 829), 8 (n = 786), and 11 years (n = 644). Based on prospective data (questionnaires, skin tests, IgE), children were assigned to wheeze phenotypes (no wheezing, transient, late-onset, and persistent) and atopy phenotypes (no atopy, dust mite, non–dust mite, multiple early, and multiple late). We used longitudinal linear mixed models to determine predictors of change in sRaw over time. Measurements and Main Results: Contrary to the assumption that sRaw is independent of age and sex, boys had higher sRaw than girls (mean difference, 0.080; 95% confidence interval [CI], 0.049–0.111; P < 0.001) and a higher rate of increase over time. For girls, sRaw increased by 0.017 kPa ⋅ s−1 per year (95% CI, 0.011–0.023). In boys this increase was significantly greater (P = 0.012; mean between-sex difference, 0.011 kPa ⋅ s−1; 95% CI, 0.003–0.019). Children with persistent wheeze (but not other wheeze phenotypes) had a significantly greater rate of deterioration in sRaw over time compared with never wheezers (P = 0.009). Similarly, children with multiple early, but not other atopy phenotypes had significantly poorer lung function than those without atopy (mean difference, 0.116 kPa ⋅ s−1; 95% CI, 0.065–0.168; P < 0.001). sRaw increased progressively with the increasing number of asthma exacerbations. Conclusions: Children with persistent wheeze, frequent asthma exacerbations, and multiple early atopy have diminished lung function throughout childhood, and are at risk of a progressive loss of lung function from age 3 to 11 years. These effects are more marked in boys.